Coping with faculty stress - Gmelch, Walter H. (Walter Howard), 1947- (Survival skills for scholars, 1993)
This useful book outlines the chief forms and major causes of academic stress. Practical advice shows how to distinguish negative from positive stress and how to deal with negative stressors in life and at work. The book includes exercises to help the academic understand how stress affects him or her, as well as forms to help design programmes for coping with stress.